Improving Arabic Language Skills With A Project-Based Approach: تحسين مهارات اللغة العربية بالمنهج القائم على المشاريع - Mukhlisah, Mukhlisah; Sirda, Win Khamsy (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Learning Arabic with a project-based curriculum approach has become a new trend in the world of language teaching. This approach allows students to develop Arabic language skills in an integrated manner through authentic and meaningful project activities. Project-based curriculum is a student-centered learning approach that integrates knowledge across disciplines through project work. This approach aims to encourage students to build a deeper understanding of the concepts studied by applying them to real contexts through project work.This article discusses the theoretical basis, characteristics, implementation, as well as the advantages and challenges of implementing a project-based curriculum in an educational environment. This approach aims to increase learning motivation, critical thinking skills, collaboration and meaningful mastery of the material. However, its implementation requires careful preparation and planning from educators, as well as good classroom management skills to make it easier for students during the project work process.